Studies on nutritional composition and characterization of lipids of Lates calcarifer (Bhetki) (Bangladesh Journal of Scientific and Industrial Research, 2013)
Physico chemical characteristics of lipids extracted from Lates calcarifer and nutritional composition of that fish were analyzed by standard method. The coefficient of viscosity was 447.69 millipoise at 30°C and specific gravity and refractive index were 0.98 and 1.37 at 30°C respectively. Saponification value, saponification equivalent, iodine value, peroxide value, acid value, ester value and reichert-meissel value were found 95.50, 286.96, 62.81, 52.59, 1.83, 193.67 and 2.94 respectively. Percentage of free fatty acid, unsaponificable matter and cholesterol were found 0.92, 1.86 and 13.74 respectively. Further, carbohydrate, protein, lipid, moisture, ash and dry matter content of L. calcarifer were found 0.93, 23.5, 5.7, 70, 5 and 30 % respectively. The fish was found to contain 580, 270,140, 120 and 9 mg of Na, K, Ca, Mg and Fe per 100 g respectively. However Cu and Zn were found to present in negligible amount. The fatty acid profiles L. calcarifer were identified by GLC method. Among fatty acid lauric, palmitic, oleic and stearic were found to present 4.49, 52.86, 36.88 and 5.75% respectively. Bangladesh J. Sci. Ind. Res. 47(4), 393-400, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14068